A Numerical Model for Determining Deep Methane Flux Linked to the Free Gas Zone: Application to the Ocean Drilling Program Site 995 and Implications for Regional Deep Methane Flux at the Blake Ridge - Zheng, Zihan; Cao, Yuncheng; Xu, Wenyue; Chen, Duofu (Frontiers in Marine Science, 2022)
The lack of the quantification of deep dissolved methane flux prevents us from accurately understanding hydrate accumulation and distribution at a given geologic setting where vertically upward methane advection dominates the hydrate system. The upward deep methane flux was usually applied as an assumed value in many previous studies. Considering the deep methane flux changes the methane concentration in the pore water and further affects the phase transfer between the gas and aqueous phases depending on the in situ methane concentration, we link gas bubbles distribution to deep dissolved methane flux. Here, we constructed a numerical model to quantify the dissolved methane flux from depth based on the parameters related to gas bubble distribution, including the residual gas saturation in sediments and the free gas zone (FGZ) thickness. We then applied our model to ODP Site 995 at the Blake Ridge where methane was sourced from deep layers. Our model results predict an upward deep methane flux of 0.0231 mol/m2/a and the occurrence of another gas interval in deeper sediments, which are consistent with seismic data. We further explored the influence of upward methane flux on hydrate accumulation and found that the thin hydrate occurrence zone at nearby Site 994 likely resulted from a small deep methane flux. Combined with the previous conclusion of high deep methane flux at Site 997, we showed that along the Blake Ridge drilling transect the estimated deep methane fluxes decrease with increasing distance from the crest of the ridge. This approach for quantifying deep methane flux is complementary to the current hydrate accumulation model and provides new insights into the regional methane flux estimation at the Blake Ridge.